The impact of Accounting Information System on Internal Audit Effectiveness: the moderation of Audit Committee in Oman - Alsabti, Haider Alaaldin Abdul Wahab (Tanjong Malim, 2022)
The impact of Accounting Information System on Internal Audit Effectiveness: the moderation of Audit Committee in Oman by Alsabti, Haider Alaaldin Abdul Wahab